Attractiveness of white clover (Trifolium repens L.) and plum (Prunus salicina Lindl. cv. Sapphire) flower volatiles to female Frankliniella occidentalis (Pergande, 1895) - Allsopp, Elleunorah; Dewhirst, Sarah; Knipe, Muriel; Prinsloo, Goddy (African Entomology, 2022)
Producers in the Western Cape province of South Africa are looking towards a push-pull strategy to reduce oviposition damage to plums by western flower thrips (WFT). White clover, Trifolium repens L., a favoured host plant of WFT, was investigated as a possible trap crop to provide the “pull” element. The attractiveness of collected volatiles of white clover flowers and of unopened (balloon stage) and open plum (Prunus salicina Lindl. cv. Sapphire) blossoms to WFT females was determined, using a Y-tube olfactometer. E-β-Farnesene, a known attractant for WFT, was included as positive control. Clover flower and open plum blossom volatiles exhibited statistically significant attraction of 69% and 71%, respectively, to WFT females. E-β-Farnesene and balloon stage plum blossom volatiles attracted 63% and 65% of WFT, respectively. When compared directly, 69% of WFT females chose the arm with the plum blossom volatiles over the clover flower volatiles. The clear preference shown by WFT for plum blossom volatiles indicates the use of a semiochemical to deter WFT from the plum blossoms would be required to enhance the efficacy of white clover as a trap crop in a push-pull strategy.